2018
DOI: 10.3892/etm.2018.6234
|View full text |Cite
|
Sign up to set email alerts
|

Anti‑neuropilin‑1 monoclonal antibody suppresses the migration and invasion of human gastric cancer cells via Akt dephosphorylation

Abstract: Neuropilin-1 (NRP-1) is involved in a range of physiological and pathological processes, including neuronal cell guidance, cardiovascular development, immunity, angiogenesis and the pathogenesis of cancer. Targeting of NRP-1 is considered to be a potential cancer therapy and a number of approaches have been investigated, including the use of small interfering RNA, peptides, soluble NRP antagonists and monoclonal antibodies. The present study used a novel anti-neuropilin-1 monoclonal antibody (anti-NRP-1 mAb) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…This indicates that immunotherapy targeting NRP1 may have good clinical outcomes [42]. NRP1 has also been previously found to promote tumour angiogenesis, tumour proliferation, and migration [43][44][45][46][47][48]. Anti-NRP1 therapy can block tumour angiogenesis and upregulate the antitumour immune response [49][50][51][52].…”
Section: Biomed Research Internationalmentioning
confidence: 94%
“…This indicates that immunotherapy targeting NRP1 may have good clinical outcomes [42]. NRP1 has also been previously found to promote tumour angiogenesis, tumour proliferation, and migration [43][44][45][46][47][48]. Anti-NRP1 therapy can block tumour angiogenesis and upregulate the antitumour immune response [49][50][51][52].…”
Section: Biomed Research Internationalmentioning
confidence: 94%
“…Published data have shown that the analysis of NRP1 expression levels could provide a predictive marker of clinical outcome and prognosis in gastric cancer [ 5 , 21 , 26 , 27 ]. Also, it is an exciting and challenging endeavor to employ NRP1-inhibitory strategies for cancer treatment [ 6 , 28 ]. Therefore, studies on the relationship of NRP1 expression and clinicopathological characteristics of GC by IHC emerged with inconclusive results from different publications.…”
Section: Discussionmentioning
confidence: 99%
“…In gastric cancer (GC), high expression of NRP1 is closely related to the development of tumor progression and associated with poor overall survival [ 5 ]. Furthermore, recent report indicated that anti-NRP-1 mAb might be a novel therapeutic approach in the treatment of gastric cancer [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…NRP1 promotes tumor cell growth, migration, invasion, and survival by interacting with several growth factors and their cognate signaling receptors. [ 92 96 ] Binding of VEGFA to NRP1 promotes RhoA activation and then, activated RhoA contributes to the degradation of p27kip1, which in turn, promotes tumor cell proliferation. This has been demonstrated in skin cancer, prostate cancer, and glioblastoma [ 60 , 97 99 ] [Figure 4 ].…”
Section: Nrp1 Promotes Tumor Proliferation and Migrationmentioning
confidence: 99%